THE NECESSITY OF TEACHING RUSSIAN LANGUAGE FOR HIGHER MEDICAL UNIVERSITIES - Xidayeva Dilorom Erkinovna (Western European Studies, 2024)
This article is devoted to the question of the need to study the Russian language in medical universities. This need is justified by the obligatory possession of not only professional, but also communicative competence by doctors.
Keywords: medicine; Russian language; doctor; patient